İslam aile hukukunda rabîbe (üvey kız çocuğu) - Tavan, Zehra (My University, 2025)
Fıkıh ilminin bir alt branşı olan aile hukukunda temel konulardan biri nikahtır. Evlenme akdinde tarafların dinen evlenmeye uygun olması yani evlenmesi yasak olan kişilerden olmaması gerekmektedir. Kur'an-ı Kerîm'de çeşitli ayetlerde “muharremât” denilen evlenmesi yasak olan kadınlar detaylıca sayılmış ve bir çerçeve oluşturulmuştur. Günlük hayatta kullanılan mahrem terimi daha geniş bir anlam ifade etmekte, evlenilmesi yasak olan erkek ve kadın hısımları kapsamaktadır. Nisâ Suresi 4/ 23. ayette ise kan hısımlığından, sıhrî hısımlıktan ve süt hısımlığından kaynaklı olarak erkeğin kendileriyle evlenmesi yasak olan kadınlara örnekler verilmiştir. Bu ayette geçen “kendileriyle zifafa girilen kadınların kızları olan ve evlerinde bulunan üvey kızlar” olarak açıklanan rabâib terimi sıhri hısımlardandır, yani bir evlilik bağı münasebetiyle kendisiyle evlenilmesi üvey babasına haram olmuştur. Rabîbe kelimesinin çoğulu olan rabâib ifadesi Kur’an-ı Kerim’de sadece bu ayette geçmektedir. Erkeğin eşinin furûu, alt soyu da denilen rabîbe, üvey kız demektir ve eğer annesinin evliliği fiilen başlamışsa yani zifaf gerçekleşmişse üvey kız, üvey babaya haramdır, evlenmeleri daimi olarak yasaktır. Ebeveynlerden birinin çocukla kan bağının olmadığı üvey aile yapısında ise üvey kızın üvey baba ile beraber yahut üvey kardeşleriyle beraber aynı evde yaşayıp yaşayamayacağı, rabîbenin hangi şartlar yerine getirilirse üvey babasına haram olduğu, ayette kastedilen duhûl lafzının kapsamı gibi hukuki meseleler ortaya çıkmıştır. Tezin amacı da hayatın içinden olan bu meseleye dair özel bir çalışma yaparak, konuyla alakalı karşılaşılan güncel problemlere değinmektir. Bu çalışmada öncelikle rabîbe kavramının konumunu İslam hukuku içerisinde daha iyi kavrayabilmek için muharremât konusuna değinilmiş, rabîbenin tanımı verilmiş, Türk hukukunda evlenme engellerinden ve rabîbenin medeni hukuktaki yerinden söz edilmiştir. Ayrıca bu kavramın geçtiği ayetin ışığında özellikle rabîbeyi haram kılan şartlar çerçevesinde konu detaylı olarak ele alınmış ve rabîbe etrafında şekillenen bazı hukuki neticeler, fıkhi kaynaklar ışığında derlenerek tezin temel konusunun daha anlaşılır bir halde sunulması hedeflenmiştir.

One of the basic issue in family law, which is a sub-branch of the science of fiqh, is marriage. In the marriage contract, the parties must be suitable for marriage in religion, that is, they must not be among those who are forbidden to marry. In the Holy Qur'an, in various verses, women who are forbidden to marry, called “muharremât”, are listed in detail and a framework is established. The term mahram, which we also use in daily life, has a wider meaning and includes male and female relatives who are forbidden to marry. In Surah Nisâ, verse 23, it gives examples of women who are forbidden to marry because of blood kinship, marital kinship and milk kinship. The term rabâib, which is explained in this verse as step-daughters who are the daughters of the women with whom you have consummated your marriage and who are in your houses, is a marital kinship, that is, it is forbidden for her stepfather to marry her because of a marital tie. The term rabâib, which is the plural of the word rabîba, is only mentioned in this verse in the Holy Qur'an. The term rabîba, which can also be called the offspring of a man's wife, means stepdaughter, and if the marriage of her mother has actually begun, that is, if sexual intercourse has taken place, the stepdaughter is forbidden to the stepfather, and they are permanently forbidden to marry. In cases where one of the parents has no biological connection to the child, as in the case of stepfamilies, various legal issues arise—such as whether a stepdaughter may live in the same house with her stepfather or step-siblings, under what conditions the stepdaughter becomes permanently unlawful (haram) for the stepfather to marry, and the scope of the term duhûl as mentioned in the relevant verse. The aim of this thesis is to conduct a focused study on this real-life issue and address contemporary problems related to it. In order to better understand the position of the concept of rabîba (stepdaughter) within Islamic law, the study first touches upon the broader topic of muharremât (those whom one is permanently forbidden to marry). The definition of rabîba is provided, and the concept is then examined within the framework of Turkish civil law, particularly in the context of legal impediments to marriage and the place of rabîba in modern legal terms. Furthermore, based on the verse in which this term is mentioned, the study explores in detail the conditions under which a rabîba becomes unlawful for her stepfather. Legal implications that revolve around the concept of rabîba are also compiled and analyzed in light of Islamic jurisprudential sources, with the aim of presenting the main subject of the thesis in a clearer and more comprehensible manner. Rabîba, stepdaughter, judgement, muharramât
The rabîba (step-daughters) in Islamic family law
Keywords: Adoption; Aile hukuku (İslam hukuku); Dini yönleri; Domestic relations (Islamic law); Evlat edinme; evlenme engeli; Fıkıh; hüküm; Islam; İslam; judgement; muharramât; muharremât; Rabîba; Rabîbe; Religious aspects; stepdaughter; üvey evlatkız